PERSPECTIVES OF DEVELOPMENT OF GREEN JOBS IN BULGARIA - Stoyanova, Zornitsa; Harizanova, Hristina (Economics of Agriculture, 2015)
The transformation to green sectors of the economy in Bulgaria leads after it the need of new type of professions, which would be capable to cope with the new conditions and requirements which different businesses are facing. The knowledge of creation of green jobs in Bulgaria is insuffcient, which makes this paper state of art. Green jobs in Bulgaria are connected with transfer of business activities to green ones. The paper analyzes and evaluates the current conditions of creation of green jobs in Bulgaria. It is proposed analysis of the requirements in Bulgaria about the eligible criteria to apply for funding under the measurement of green jobs; based on research SWOT analysis of creation of green jobs. The results are systematized in fndings, conclusions and policy recommendations, as changing conditions of applying to measurement, payment connected to employees, and etc. As well is proposed cooperation between other existing measurements for reaching sustainable employment in Bulgaria.